Herbicidas dessecantes na fauna edáfica e genotoxicidade - Reimche, Geovane Boschmann (2014)
The use of direct seeding system brought changes on the weed management, by the mean of increasing of chemical control. The intense use of herbicides may have effect over the ecology of non-target soil organism. Two studies were conduct aiming testing the effect of herbicides over composition of soil mesofauna under genetically modified glyphosate resistance soy (RR®) (Chapter I) and assess the cito- genotoxicity effect of glyphosate, ammonium gluphosinate, paraquat and saflufenacil herbicide, applied during non-selective operation spray, before soy seeding (Chapter II). In Chapter I, results showed that in both agricultural years, soil mesofauna was dominate by Acari followed by Collembola, were Oribatida and Entomobryomorpha were the most predominating, respectively. In Chapter I, results showed of ammonium glufosinate favored an increase of springtails (Entomobryomorpha) and mites (Eupodes sp. Scheloribates sp. Galumnidae and Mesostigmata). Paraquat favored springtails (Entomobryomorpha) and mites (Pygmephoridae, Scheloribates sp. and Mesostigmata). Mite population (Pygmephoridae and Scheloribates sp.) increase with glyphosate treatment; and mites (Scheloribates sp.) with saflufenacil application; while in the glyphosate with saflufenacil association there was an increased springtails (Entomobryomorpha) density. The Haplotaxida Order show a greater sensitivity to glufosinato herbicides, paraquat and saflufenacil. In Chapter II, results showed that the glyphosate commercial formulation and analytical standard did not show cytotoxic effect at 5, 10 or 26ppm concentrations over the A. cepa cells; and only commercial formulation presented genotoxic. The gluphosinate shows no cytotoxic action, but tested plant cells, evidenced little genotoxic effect. Paraquat commercial formulation reduced cell division at the test concentrations (2, 4 and 11ppm) without genotoxic evidence. Saflufenacil did not affect cell division and express a weak genotoxicity using 0,25ppm concentration in plant cells test.